Demonstration Method In Introduce Secondary Color Learning - Surwayaningrat, N D E; Sumilat, J M (Journal of Educational Method and Technology, 2018)
Early childhood education is very important for the child's future.[1] early childhood is the age of gold where the development of children into a period of development is very decisive. The mix of primary colors (Red, yellow, blue), will become secondary color, and this is generally not understood by kindergarten children. To introduce the secondary color requires a method of learning that shows directly how to obtain it, such as the method of demonstration learning. The purpose of this study is to improve the ability to recognize the secondary color in children with the method of demonstration learning. This research uses Class Action Research method. The subjects of this study were students of group B kindergarten GMIM Hosiana Tumatangtang amounted to 14 children. The results obtained through two cycles with the application of demonstration methods can improve the ability to introduce secondary color. Keywords : Introduce Secondary Color, Demonstration Method.